2014
DOI: 10.1007/s00132-014-2296-0
|View full text |Cite
|
Sign up to set email alerts
|

Meldepflichtige Vorkommnisse mit Operationsinstrumenten in der Orthopädischen Chirurgie

Abstract: Such consequences of instrument failure were considered to be a reportable incident. A thorough documentation as well as incident reporting to the manufacturer and the Federal authorities are required for a sufficient processing and risk assessment of the incident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In the maxillofacial speciality the authors reported 7 incidences out of 548 operations [ 5 ]. According to Kluess et al ., it is important that any incident with orthopaedic surgical instruments should be reported to the manufacturer and the health authorities for sufficient processing and risk assessment of the accident [ 6 ]. In the case of some reusable metal instruments both titanium alloys and stainless steel are in the high performance range.…”
Section: Case Presentationmentioning
confidence: 99%
“…In the maxillofacial speciality the authors reported 7 incidences out of 548 operations [ 5 ]. According to Kluess et al ., it is important that any incident with orthopaedic surgical instruments should be reported to the manufacturer and the health authorities for sufficient processing and risk assessment of the accident [ 6 ]. In the case of some reusable metal instruments both titanium alloys and stainless steel are in the high performance range.…”
Section: Case Presentationmentioning
confidence: 99%